A ZnO driven silicon cantilever for nanoscale actuation - Yuan, Yanhui (2013)
A micro silicon cantilever actuated by ZnO thin film was designed, fabricated and characterized. The ZnO thin film was deposited by RF sputtering at room temperature. The transverse piezoelectric constant d31 was found to be-4.66 pC/N. Time and frequency responses of the cantilever actuator were investigated by means of a laser Doppler vibrometer. The actuator has a sensitivity of 12 nm/V at 15 kHz. Its 1st bending resonance was observed at 53 kHz. The bandwidth was found to be 27 kHz with damping of 0.35%. The cantilever demonstrated capability of high frequency actuation on a nanometer level.